STRESS BETWEEN PRACTICING AND NON-PRACTICAL TRANSIT AGENTS OF PHISICAL EXERCISES (Fiep Bulletin - online, 2020)
Nowadays stress has become more and more present in workplaces, due to such phenomenon, this study aims to compare the level of stress between practicing and non-practicing traffic agents of the Traffic and Patos - PB Transport Superintendence. -PB. The sample consisted of 35 subjects of both sexes aged 31 to 46 years divided into two groups G1 = 22 exerciser and G2 = 13 non-exerciser. The instruments used were: a socio demographic questionnaire and job perception data and the LIPP (ISS test). The results indicate that 54.54% of the subjects belonging to G1 do not fit in any phase, being characterized by the absence of stress; in relation to G2 it can be observed that 69.23% of the subjects had some stress symptom. As evidenced in the literature that the practice of physical exercise plays an essential role in the prevention and treatment of physical and psychological diseases, this study confirms that the practice of physical exercise is linked to lower stress rates in traffic agents.